(3OhQ GdOdGdI h GdSjGb ai GdJbYjO GdfMhi Hjf YHOGdbGgQ GdLQLGfi h GdReNTQi (B/ s - (3QGHMI eMeO VYjf SYO GdQTjOis; (3MSf WHd (B: s; (3eMeO GdYeQGhi (B: s ((3GdbGgQI (B: s (3QGHMI eMeO VYjf SYO GdQTjOi (B: s, 2018)
(3GbJVJ WHjYI gPg GdOQGSI GdJi Hjf jOi GdYdeGA GdCaGVd Cf JCJj ai ebOeI hJ egjO h CQHYI aUhd h NGJeI(B: (3CeG GdebOeI abO JfGhndrJ gOna GdHMK(B: (3h OhGaY GNJjGQg(B: (3h efgnLg(B: (3h NWI GdHMK ajg(B. (3h GgJe GdJegjO HJYQja YHOGdbGgQ h GdReNTQi HEjLGR ef fhGmM YOjOI; efgG GdCUd h GdfSH h GdCSQI(B: (3h GdehdO h GdfTCI(B: (3h GdJYdje h GdTjhN(B: (3h ZjoQgG(B. (3ceG GgJe GdJegjO CjkVG HEYWGA acQI Yf GdOdGdI h GdSjGb(B. (3NpqUU GdaUd GdChd ddOdGdI GdUhJjI Hjf YHOGdbGgQ h GdReNTQi(B: (3h bO LGA aj KdGKI eHGMK(B: (3GdChd(B: (3NUGFU GdUhJ YfO YHOGdbGgQ h GdReNTQi(B: (3h GdKGfi(B: (3JBda GdCUhGJ h JZjQGJgG YfOgeG(B: (3h GdKGdK(B: (3YdGbI GdUhJ HGdOdGdI YfOgeG(B. (3h JfGhd GdaUd GdKGfi GdOdGdI GdUQajI Hjf YHOGdbGgQ h GdReNTQi(B: (3h LGA ai JhWFI h eHMKjf(B: (3GdChd(B: (3OdGdI GdUjZ GdUQajI YfO YHOGdbGgQ h GdReNTQj(B: (3h GdKGfi(B: (3OdGdI GdeUGOQ h GdeTJbGJ YfOgeG(B. (3h bO JfGhd GdaUd GdKGdK GdLhGfH GdOdGdjI ai hXGFa GdLedI Hjf YHOGdbGgQ h GdReNTQi(B: (3ceG LGA ai JhWFI h eHMKjf(B: (3GdChd(B: (3GdOdGdI ai GdYfGUQ GdESfGOjI YfO YHOGdbGgQ h GdReNTQi(B: (3h GdKGfi(B: (3GdOdGdI ai ecedGJ GdLedI YfOgeG(B. (3CeG GdaUd GdQGHY h GdCNjQ abO anqUd GdcdGe Mhd OdGdI GdSjGb h CKpQgG ai GdJQGcjH GdfMhjI YfO YHOGdbGgQ h GdReNTQi(B: (3h Pdc aj JhWFI h eHMKjf(B: (3GdChd(B: (3OdGdI GdSjGb h CKQgG ai GdMPa h GdPcQ YfO YHOGdbGgQ h GdReNTQi(B: (3h GdKGfi(B: (3OdGdI GdSjGb h CKQgG ai GdJbOje h GdJCNjQ YfOgeG(B. (3h JCJi GdNGJeI dJYQV Cgnqe GdfJGFL GdJi NQLJ HgG GdOQGSIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe GdfMh h GdUQa h GdYQhVs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdOdGdIs; (3GdReNTQis; (3YHOGdbGgQ GdLQLGfis